A global strategy for the conservation and use of cacao genetic resources, as the foundation for a sustainable cocoa economy - Lberté, B.; CacaoNet; Bioversity International (2012)
The Global Strategy for the Conservation and Use of Cacao Genetic Resources, developed by the Global Network for Cacao Genetic Resources (CacaoNet). The strategy is the result of a consultation process that drew upon the global cocoa community’s expertise in all aspects of cacao genetic resources. The vision of the Global Strategy is to improve the livelihoods of the 5-6 million farmers in developing countries across tropical Africa, Asia and Latin America and the 40-50 million people who depend upon cocoa for their livelihoods. The specific goal is to optimize the conservation and maximize the use of cacao genetic resources as the foundation of a sustainable cocoa economy by bringing together national and international players in public and private sectors who will work towards the establishment of an endowment fund for the conservation and use of the most valuable resources in perpetuity. There are 2 versions of the Global Strategy for Cacao Genetic Resources Conservation and Use: 1) Full document – 176 pages 2) Summary booklet – 25 pages